2020
DOI: 10.1111/jfbc.13565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the polyphenol‐rich extract fromAllium cepaon hyperlipidemic sprague‐dawley rats

Abstract: Allium cepa is used for the prevention and treatment of hyperlipidemia-related diseases such as atherosclerosis in the folk. This study was mainly aimed at investigating the effects of A. cepa extract (ACE) enriched in polyphenols on hyperlipidemia Sprague-Dawley (SD) experiment rat models. The levels of total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), malondialdehyde (MDA), and superoxide dismutase (SOD) activity in serum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Supporting the present finding, sulphur compounds, such as cycloalliin, S -methyl-L-cysteine, S -propyl-L-cysteine sulphoxide, dimethyl trisulphide, and especially S -methyl-L-cysteine sulphoxide, were reported to be effective in inhibiting formation of oil drop in the cells, suggesting that these compounds may be involved in the antiobesity effect of the onion extract [ 45 ]. Therefore, the present results are in agreement with those reported in the literature showing lipid-lowering effects of different Allium cepa and apple products or extracts [ 15 , 46 , 47 ]. Regarding glycemia and insulinemia, a marked and significant reduction in plasma glucose and insulin in OO group (−35% and −49%, respectively) compared to OC group was found; meanwhile, plasma glucose and insulin levels in OA group were lower than in OC group, but less pronounced (−23%, −34%; respectively).…”
Section: Resultssupporting
confidence: 94%
“…Supporting the present finding, sulphur compounds, such as cycloalliin, S -methyl-L-cysteine, S -propyl-L-cysteine sulphoxide, dimethyl trisulphide, and especially S -methyl-L-cysteine sulphoxide, were reported to be effective in inhibiting formation of oil drop in the cells, suggesting that these compounds may be involved in the antiobesity effect of the onion extract [ 45 ]. Therefore, the present results are in agreement with those reported in the literature showing lipid-lowering effects of different Allium cepa and apple products or extracts [ 15 , 46 , 47 ]. Regarding glycemia and insulinemia, a marked and significant reduction in plasma glucose and insulin in OO group (−35% and −49%, respectively) compared to OC group was found; meanwhile, plasma glucose and insulin levels in OA group were lower than in OC group, but less pronounced (−23%, −34%; respectively).…”
Section: Resultssupporting
confidence: 94%
“…These plaques causes narrowing and/or blocking of the blood vessels which disrupts blood flow in vital organs of the body such as heart and brain and thereby raising the risk of heart attack and stroke. A study performed by Wenyi Li et al to assess the antihypercholesterolemic activities of A. cepa on six groups of hyperlipidemic rats showed that there was a substantial decrease in total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-c) levels, and a raise in high density lipoprotein cholesterol (HDL-c) levels in both plasma and liver following 4 weeks of oral administration of A. cepa extract at different concentration for each group of rats [ 106 ]. Ming and his group of researchers performed a clinical trial on twenty-four mildly hypercholesterolemic adults to determine the effectiveness of onion juice against this condition, and the results showed that, after eight weeks of daily administration, the blood plasma TC, LDL-c, and LDL-c/HDL-c ratio levels were significantly lowered in onion juice treated subjects.…”
Section: Therapeutic Potential Of Allium Cepamentioning
confidence: 99%
“…In an animal model study conducted by Li and colleagues revealed that the decrease of the plasma LDL-C content by 45% in the onion-fed group was associated with the inhibition of HMGR and the upregulation of LDLR expression, which was a plausible mechanism for its LDL-C lowering effect. Researchers concluded that this effect was due to the presence of quercetin and isoquercitrin in onion [79]. Polyphenols-rich grape extract capsules (300 mg/day) were orally given to obese individuals for a period of 12 weeks.…”
Section: Dietary Polyphenols: Potential Ldl-c Lowering Agentsmentioning
confidence: 99%